PEMBUATAN MEDIA PEMBELAJARAN SISTEM REM CAKRAM BERBASIS ANDROID - Firyal Agung Azmi, - (2022)
Abstract. This thesis research discusses the manufacture of learning media for android-based disc brake systems with the aim of knowing how to make android-based learning media, knowing the feasibility of learning media, and knowing the responses of students. The occurrence of COVID-19 which resulted in learning being done online which resulted in distance learning and learning media still using conventional. In this case, an Android-based learning media is made to make it easier for students to find material, facilitate students in learning, make learning media more interactive and help educators in the teaching and learning process. The method used in this study uses research and development methods with the ADDIE model. The results of research on learning media for this android-based disc brake system, the first is on making learning media using a design, development, implementation, and evaluation analysis model, the second is the validity results from material experts consisting of learning aspects with a score of 94% and content aspects with a score of 88%, overall from material experts got a score of 91% which was declared "very feasible", the results of the validity of media experts consisting of the display aspect with a score of 91% and the programming aspect with a score of 92%, overall from media experts was 91 .5% which was declared "very feasible", and the third was regarding the results of student responses which consisted of the linguistic aspect with a score of 91% which was categorized as "very feasible", the programming aspect with a score of 91% which was categorized as "very feasible", the display aspect with a score of 89% which is categorized as "very feasible", and the implementation aspect with a score of 92% which is categorized as "very feasible", overall and The students' responses got a score of 90.75% which was categorized as "very feasible" by the students. which can be concluded that the learning media from media experts, material experts, students are declared "very feasible"